62 Changing preference for, and actual place of death, among palliative care patients: a secondary data analysis. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Khamis, Assem; Bradshaw, Andy; Davies, Joanna; Landon, Alison; Dodds, Nigel; Proffit, Amy; George, Rob; Boland, Jason; Santarelli, Martina; Sartain, Kath; Ross, Joy; Richardson, Heather; et al.
Abstract : Background: Place of death has been used as a quality indicator. However, evidence on changes in preferences for place of death remains limited. This study describes preferred and actual place of death, plus changes, among patients who died while receiving inpatient and community palliative care. Methods: Secondary analysis of routinely-collected clinical and outcomes data between June-November 2019. Inpatient hospice and community settings were included; for each setting, we compared first-documented preferred place of death with the latest-documented preference across the episode of care. We also compared the latest-documented preferred place with actual place of death. Caldicott Guardian approval was received for analysis of this anonymized data. Results: 269 patients received 277 complete episodes of care in the inpatient unit, and 510 patients received 527 complete episodes of community-based palliative care. Median age for inpatients was 75 years (IQR 63 '' 83) compared with 81 years (IQR 71 '' 89) for community. 82% inpatients had cancer compared with 63% in the community. 98% inpatients had no documented change in preferred place of death (69% and 27% preferred hospice or home, respectively). 92% community patients had no documented change in preferred place of death (74% preferred home). We compared the latest-documented preferred place with actual place of death. Two thirds of inpatients (66%) preferred and died at the hospice, while 27% preferred home, but died in hospice. In the community, 57% of patients preferred and died at home, while 19% preferred home, but died elsewhere (in hospital or nursing/residential home). Conclusion: There is high concordance between preferred and actual place of death among both inpatients and community palliative care patients in this cohort; with the exception of some hospice inpatients who prefer home but die elsewhere. Change in preference for place of death are very infrequently reported. Funding: Supported by Yorkshire Cancer Research (L412)